Mechanisms of Integration of the Republic of Kazakhstan in the Processes of Global Competition - Gabdullin, R. (Наука та інновації, 2013)
This article considers issues related to integration of national economy of Kazakhstan in global microeconomic processes
and also issues of formation of highly industrial economy based on innovational modernization of priority industries and sectors. Besides this assignment the article comprise contains comprehensive practical recommendations for optimization of Kazakhstan economy structure during post-crisis development through activation of institutes of development. У статті розглядаються питання інтеграції національної економіки Казахстану в глобальні світогосподарські
процеси, а також формування високоіндустріальної економіки на основі інноваційної модернізації пріоритетних
галузей і сфер. Крім того робота містить комплексні
практичні рекомендації щодо оптимізації структури економіки Казахстану в посткризовий період розвитку шляхом активізації інститутів розвитку. В статье рассматриваются вопросы интеграции национальной экономики Казахстана в глобальные мирохозяйственные процессы, а также формирования высокоиндустриальной экономики на основе инновационной
модернизации приоритетных отраслей и сфер. Кроме
того, работа содержит комплексные практические рекомендации по оптимизации структуры экономики Казахстана в посткризисный период развития посредствам активизации институтов развития.